FORMULASI DAN UJI STABILITAS FISIK SERUM SPRAY EKSTRAK UMBI WORTEL (Daucus carota L.) SEBAGAI ANTI AGING - Ermawati Ermawati (Jurnal Kesehatan Yamasi Makassar, 2022)
Carrots have the potential to be anti-aging because of its antioxidant content as an anti-aging. This study aims to make a carrot tuber extract spray serum and to determine the physical quality test of carrot tuber extract spray serum preparations (Daucus carota L.). The extraction method used is maceration. Then proceed with the manufacture of serum spray. The results showed that carrot tuber extract can be used in the manufacture of serum spray preparations as an anti-aging and fulfilling physical quality tests.